What is the solution set of 2x(x - 1) = 3?

Question

Asked 5/3/2014 2:04:58 PM

Updated 5/21/2014 9:33:21 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/21/2014 9:30:12 PM]

2x - x = -5 - 3;

x = -8

jshafer|Points 140|

= 7x + 3x + 4 - 3

= 10x + 1

= 10x

jeifunk|Points 22064|

jeifunk|Points 22064|

jeifunk|Points 22064|

drop3v8|Points 175|

Question

Asked 5/3/2014 2:04:58 PM

Updated 5/21/2014 9:33:21 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/21/2014 9:30:12 PM]

Rating

3

2x(x - 1) = 3

2x^2 - 2x - 3 = 0

b^2 - 4ac = (-2)^2 - 4(2)(-3) = 28

x = [-b ± sqrt (b^2 - 4ac)]/2a

= (2 ± sqrt 28)/4

= (2 ± 2 sqrt 7)/4

= (1 ± sqrt 7)/2

2x^2 - 2x - 3 = 0

b^2 - 4ac = (-2)^2 - 4(2)(-3) = 28

x = [-b ± sqrt (b^2 - 4ac)]/2a

= (2 ± sqrt 28)/4

= (2 ± 2 sqrt 7)/4

= (1 ± sqrt 7)/2

Added 5/21/2014 9:29:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/21/2014 9:40:50 PM]

3

7x^2 + 3x = 0

x(7x + 3) = 0

x = 0 or x = -3/7

The solution set for 7x^2 + 3x = 0 is {0, -3/7}.

x(7x + 3) = 0

x = 0 or x = -3/7

The solution set for 7x^2 + 3x = 0 is {0, -3/7}.

Added 5/21/2014 9:31:50 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/21/2014 9:36:11 PM]

3

(x - 2)(x - 3) = 2

x^2 - 3x - 2x + 6 = 2

x^2 - 5x + 4 = 0

(x - 1)(x - 4) = 0

x = 1 or x = 4

The solution set for (x - 2)(x - 3) = 2 is {1, 4}

x^2 - 3x - 2x + 6 = 2

x^2 - 5x + 4 = 0

(x - 1)(x - 4) = 0

x = 1 or x = 4

The solution set for (x - 2)(x - 3) = 2 is {1, 4}

Added 5/21/2014 9:33:21 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/21/2014 9:36:14 PM]

29,978,855

questions answered

There are no comments.